An experimental assessment of using waste plastic fuel as an additive in a DI diesel engine running on Jatropha biodiesel blends. (June 2023) - Kumar, Rajan; Misra, Manoj Kumar; Roy, Manish Kumar
The sole objective of the current work is to assess the effects of adding waste plastic fuel to diesel and jatropha biodiesel. In order to test this, seven distinct fuel samples made up of jatropha biodiesel-diesel, WPF-jatropha biodiesel-diesel, and regular diesel as a reference fuel were created using predefined volumetric proportions. After thorough characterization, studies are carried out employing spectroscopic methods such as FTIR, elemental analysis, and GC-MS. Finally, a direct-injection single-cylinder diesel engine underwent performance and emission tests. It has been discovered that adding WPF to biodiesel lowers its density, flash point, and viscosity. When WPF is added to biodiesel blends, the biodiesel's cold flow properties are improved, and its calorific value and diesel index are raised. According to FTIR analysis of the fuel samples, the WPF mixed biodiesel, biodiesel, and diesel all share certain common functional groups. According to GC-MS examination of the fuel samples, all of the blends contain some aliphatic and aromatic chemicals as well as diglycerides, triglycerides, and ester components. WPF blended fuels exhibit improved thermal efficiency under partial loading situations, according to engine performance tests. It is discovered that the WPF blended fuel has a lower exhaust temperature than biodiesel. Compared to biodiesel and diesel, WPF mixed fuel has higher HC emissions but lower NOx emissions. Thus, it is advantageous to mix waste plastic fuel with biodiesel because doing so lowers NOx emissions while simultaneously raising the calorific value and diesel index of the biodiesel.